Effects of Foot and Hand Massage on Pain of Open Heart Surgery Patients in Intensive Care Units - Ghazal, Sawsan (Latakia University Journal -Medical Sciences Series, 2014)
Recovery from cardiac surgery is associated with severe chest pain at the site of sternotomy and limb pain at the site of conduit harvesting. Patients routinely report mild to moderate pain even though they were administered sedative drugs. The integration of massage therapy into the team approach in patient care constitutes a move forward that recognizes pain as the fifth vital sign after pulse, blood pressure, temperature, and respiratory rate. This study was performed on patients who had open heart surgery and had the inclusion criteria for entering the study in ICU in Bassel Center for disease and heart surgery in Lattakia. A sample of 30 male and female patients was randomly divided into two groups: control group, experimental massage group. The experimental group received hand and foot massage after surgery. Our findings demonstrate that the mean score of pain severity in both groups was not significantly different at the beginning of the study. This means that pain severity was similar in both groups at the beginning of the study before applying any intervention. Results showed that there was a significant difference between the mean score of pain severity of the intervention group and the control group, after applying hand and foot massage together. The study concludes that foot and hand massage is one of the available interventions in complementary medicine and treatment which provides an opportunity for nurses to care for their patients. يترافق التعافي من جراحة القلب مع ألم صدري شديد في موقع القص وألم الطرف في موقع الصافن، يسجل هؤلاء المرضى بشكل روتيني تدرجات خفيفة الى معتدلة من الألم على الرغم من إعطاء العقاقير المهدئة. يشكل دمج العلاج بالتدليك في نهج فريق رعاية المرضى خطوة إلى الأمام حددت الألم كعلامة حيوية خامسة بعد النبض، وضغط الدم، ودرجة الحرارة، ومعدل التنفس. وقد أجريت هذه الدراسة على عينة قوامها 30 مريضا أجريت لهم جراحة القلب المفتوح في وحدة الرعاية المركزة في مركز الباسل لأمراض وجراحة القلب في اللاذقية. تم تقسيم العينة بشكل عشوائي إلى مجموعة ضابطة ومجموعة تجريبية. تلقت المجموعة التجريبية تدليك اليد والقدم بعد الجراحة بينما تركت المجموعة الضابطة لروتين المشفى. أظهرت نتائجنا أن متوسط ​​درجة شدة الألم في كلا المجموعتين لم تختلف بشكل ملحوظ في بداية الدراسة. وهذا يعني أن شدة الألم كانت متماثلة في المجموعتين في بداية الدراسة قبل تطبيق أي تدخل. وأظهرت النتائج أن هناك فرق ذو دلالة إحصائية في متوسط درجة شدة الألم ​​في مجموعة التدخل والسيطرة ، بعد تطبيق تدليك اليد والقدم معا. تدليكالقدم واليد هي واحدة من التدخلات المتاحة في الطب التكميلي والعلاج الذي يقدم فرصة للممرضين لرعاية مرضاهم. العلاج بالتدليك هو نهج علاجي يدوي تستخدم لتسهيل الشفاء والصحة ويمكن استخدامها من قبل الممرضين في أي مكان تقريبا.